A Kinetic Study of Oxalic Acid Electrochemical Oxidation on a Manganese Dioxide Rotating Cylinder Anode - Abbar,Ali H. (2018)
This paper deals with the theory and kinetics of oxalic acid electrochemical oxidation, in an acidic solution containing sodium chloride, using a manganese dioxide rotating cylinder anode. Voltammetric and galvanostatic electrolysis techniques were used. The voltametric study shows a higher anodic wave corresponding to chlorine oxidation on the MnO2 electrode, prevailing oxalic acid indirect oxidation. Galvanostatic electrolysis studies confirmed that the rate constant is affected by chloride concentration, current density, agitation and temperature. Electrochemical oxidation rate was found to be a pseudo-first order kinetic process. A strongly linear relationship between the rate constant and chloride concentration was observed, while polynomial relations, with respect to current density and temperature, were found. The activation energy was found to be 14.541 kJ/mol, which suggests a diffusion control kinetic step in oxalic acid degradation. The findings of the present research validate that oxalic acid incineration can be successfully carried out on a MnO2 anode, in NaCl presence.